2008
DOI: 10.1007/s12192-007-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the HSP90AA1 gene: distribution of polymorphisms among sheep with different responses to scrapie

Abstract: Scrapie is a transmissible spongiform encephalopathy in sheep and goats. Susceptibility to this neurodegenerative disease is mainly controlled by point mutations at the PRNP locus. Other genes, apart from PRNP, have been reported to modulate resistance/susceptibility to scrapie. On the basis of several studies in Alzheimer and different transmissible spongiform encephalopathy models, HSP90AA1 was chosen as a putative positional and functional candidate gene that might be involved in the polygenic variance ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…It codes for a chaperone protein that influences aggregation at early stages in Alzheimer's disease (Evans et al, 2006), induced microglial activation (Kakimura et al, 2002). Moreover, some polymorphisms of the HSP90AA1 gene in the promoter region modulate the gene expression and scrapie resistance in Aragonesa and Romanov sheep breeds (Marcos-Carcavilla et al, 2008). In conclusion, the QTL for scrapie incubation time on chromosome 18 has been confirmed in different PrP genotypes.…”
Section: Discussionmentioning
confidence: 81%
“…It codes for a chaperone protein that influences aggregation at early stages in Alzheimer's disease (Evans et al, 2006), induced microglial activation (Kakimura et al, 2002). Moreover, some polymorphisms of the HSP90AA1 gene in the promoter region modulate the gene expression and scrapie resistance in Aragonesa and Romanov sheep breeds (Marcos-Carcavilla et al, 2008). In conclusion, the QTL for scrapie incubation time on chromosome 18 has been confirmed in different PrP genotypes.…”
Section: Discussionmentioning
confidence: 81%
“…The CGI includes core promoter elements like a regulatory heat shock element (HSE), a consensus BRE motif, which is followed by a canonical TATA box (first described by Marcos-Carcavilla et al (2008)) and an Inr consensus motif which includes one TSS (A +1 ). They are located precisely at positions −89, −39, and −30 relative to TSS, respectively.…”
Section: Hsp90aa1 Promoter Structure and Associated Cpg Islandmentioning
confidence: 99%
“…Hsp90α is necessary for spermatogenesis and meiotic progression in mammalian testis (Grad et al 2010). The ovine HSP90AA1 gene has been studied thoroughly by our group since 2008 (Marcos-Carcavilla et al 2008, 2010aOner et al 2012;Salces-Ortiz et al 2013, 2015a. A recent functional analysis of the ovine HSP90AA1 gene (Salces-Ortiz et al 2015c) has demonstrated that two linked polymorphisms, a cytosine insertion (g.667_668insC; rs397514115) and a C to G transversion (g.660G>C; rs397514116), both located at the promoter region, are mainly responsible for the observed differences in the expression rate of the gene in response to heat stress events.…”
Section: Introductionmentioning
confidence: 99%
“…Within this region, previous results indicate that the HSP90AA1 gene, which encodes the inducible form of the cytoplasmic Hsp90α chaperone, is a good functional and positional candidate gene acting as a modulator of the response to SC in sheep (Marcos-Carcavilla et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…We previously hypothesized that after SC infection, PrP Sc starts to accumulate because its degradation is impaired (Marcos-Carcavilla et al 2008). Therefore, Hsp90 could contribute to the correct folding of PrP Sc instead of participating in other functions as the repression of heat shock factor 1 (HSF1) or the maintenance of the 26S proteasome and, thus, result in an increased expression of other heat shock proteins and in a minor proteasomal function.…”
Section: Introductionmentioning
confidence: 99%